Flow Electrification and Non-Uniform Corrosion in Low Conductivity Potable Waters. Issue 5 (16th January 2016) - Sarver, Emily; Slabaugh, Rebecca; Strock, Christopher; Edwards, Marc
Abstract : "Flow electrification" occurs whenever a fluid passes along a charged surface, creating an electrokinetic "streaming current" or "streaming potential' and is known to cause non-uniform corrosion (and other) problems in non-aqueous fluids. After observing unusual corrosion failures of copper in relatively low conductivity (≈150 μS/cm) potable water, a series of laboratory studies was conducted that verified flow electrification could also develop in aqueous systems and contribute to non-uniform corrosion. Relatively high direct streaming currents along pipelines were quantified in model systems with plastic dielectrics, which accelerated corrosion on the affected pipe section by up to 0.5 μA/cm 2 (assuming uniform corrosion). Very rapid non-uniform pipe failures (i.e., full wall penetration in 7 months) occurred in a system without dielectrics simulating a potable water recirculation system. The effects of flow electrification were virtually eliminated by addition of low levels of zinc phosphate, an inhibitor used in approximate 25% of potable water distribution systems. Flow electrification was also observed in plastic pipe systems with brass connectors.